Biomaterials for Craniofacial Bone Engineering. (December 2014) - Tevlin, R.; McArdle, A.; Atashroo, D.; Walmsley, G.G.; Senarath-Yapa, K.; Zielins, E.R.; Paik, K.J.; Longaker, M.T.; Wan, D.C.
Conditions such as congenital anomalies, cancers, and trauma can all result in devastating deficits of bone in the craniofacial skeleton. This can lead to significant alteration in function and appearance that may have significant implications for patients. In addition, large bone defects in this area can pose serious clinical dilemmas, which prove difficult to remedy, even with current gold standard surgical treatments. The craniofacial skeleton is complex and serves important functional demands. The necessity to develop new approaches for craniofacial reconstruction arises from the fact that traditional therapeutic modalities, such as autologous bone grafting, present myriad limitations and carry with them the potential for significant complications. While the optimal bone construct for tissue regeneration remains to be elucidated, much progress has been made in the past decade. Advances in tissue engineering have led to innovative scaffold design, complemented by progress in the understanding of stem cell–based therapy and growth factor enhancement of the healing cascade. This review focuses on the role of biomaterials for craniofacial bone engineering, highlighting key advances in scaffold design and development.